Detection and utility of cell-free and circulating tumour DNA in bone and soft-tissue sarcomas. Issue 9 (1st September 2021) - Tsoi, Kim M.; Gokgoz, Nalan; Darville-O'Quinn, Paige; Prochazka, Patrick; Malekoltojari, Ainaz; Griffin, Anthony M.; Ferguson, Peter C.; Wunder, Jay S.; Andrulis, Irene L.
Abstract : Aims: Cell-free DNA (cfDNA) and circulating tumour DNA (ctDNA) are used for prognostication and monitoring in patients with carcinomas, but their utility is unclear in sarcomas. The objectives of this pilot study were to explore the prognostic significance of cfDNA and investigate whether tumour-specific alterations can be detected in the circulation of sarcoma patients. Methods: Matched tumour and blood were collected from 64 sarcoma patients (n = 70 samples) prior to resection of the primary tumour (n = 57) or disease recurrence (n = 7). DNA was isolated from plasma, quantified, and analyzed for cfDNA. A subset of cases (n = 6) underwent whole exome sequencing to identify tumour-specific alterations used to detect ctDNA using digital droplet polymerase chain reaction (ddPCR). Results: Cell-free was present in 69 of 70 samples above 0.5 ng/ml. Improved disease-free survival was found for patients with lower cfDNA levels (90% vs 48% at one-year for ≤ 6 ng/ml and > 6 ng/ml, respectively; p = 0.005). Digital droplet PCR was performed as a pilot study and mutant alleles were detectable at 0.5% to 2.5% of the wild type genome, and at a level of 0.25 ng tumour DNA. Tumour-specific alterations (ctDNA) were found in five of six cases. Conclusion: This work demonstrates the feasibility and potential utility of cfDNA and ctDNA as biomarkers for bone and soft-tissue sarcomas, despite the lack of recurrent genomic alterations. A larger study is required to validate these findings. Cite this article: Bone Joint Res 2021;10(9):602–610.